2022
DOI: 10.21203/rs.3.rs-1562230/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Use of dexmedetomidine in patients with sepsis: a systematic review and meta-analysis of randomized-controlled trials

Abstract: PurposeDexmedetomidine is widely used in patients with sepsis. However, its effect on septic patients remains controversial. Therefore, the objective of this study is to summarize all randomized-controlled trials examining the use of dexmedetomidine in patients with sepsis.MethodsIn this systematic review and meta-analysis, we searched for randomized-controlled trials comparing dexmedetomidine with other sedatives in adults with sepsis. We generated pooled relative risks and mean differences, and performed tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Several systematic reviews and meta-analyses on this research topic have been previously conducted [11] [12] [13] [49] [14]. Among previous meta-analyses, Huang et al was the most comprehensive study [13], and it included 15 RCTs with 1,871 patients in the analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several systematic reviews and meta-analyses on this research topic have been previously conducted [11] [12] [13] [49] [14]. Among previous meta-analyses, Huang et al was the most comprehensive study [13], and it included 15 RCTs with 1,871 patients in the analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Recent four meta-analyses have shown controversial results, where two of these studies [11] [12] suggested a positive effect of dexmedetomidine on mortality in sepsis patients, while two other studies [13] [14] did not find a significant difference in mortality between dexmedetomidine and the other sedative agents. However, these conclusions are limited by the number of included studies, and the effects of dexmedetomidine on the incidence of delirium, adverse events, and the length of intensive care unit (ICU) stay remains controversial.…”
Section: Introductionmentioning
confidence: 99%